Association of body mass index with survival in U.S. cancer survivors: a cross-sectional study of NHANES 1999–2018 - Yang, Yi; Chen, Dan; Zhong, Dingfu; Yi, Zongbi (Frontiers in Oncology, 2023)
Background: Understanding the association between relative mortality with body mass index (BMI) may aid clinicians in making suitable clinical decisions. Our study evaluated the impact of BMI on mortality among cancer survivors. Methods: We used data from the US National Health and Nutrition Examination Surveys (NHANES) spanning from 1999 to 2018. Relevant mortality data were retrieved up until December 31, 2019. Adjusted Cox models were employed to examine the association of BMI with the risks for total and cause-specific mortality. Results: Among 4135 cancer survivors, 1486 (35.9%) were obese (21.0% class 1 obesity [BMI 30-<35 kg/m2], 9.2% class 2 obesity [BMI 35-<40 kg/m2], 5.7% class 3 obesity [BMI ≥40 kg/m2]), 1475(35.7%) were overweight (BMI 25-<30 kg/m2). During an average follow-up of 8.9 years (35895 person-years), a total of 1361 deaths were reported (cancer 392; 356 cardiovascular disease [CVD]; 613, non-cancer, non-CVD). In multivariable models, underweight participants (BMI <18.5 kg/m2) were associated with significantly higher risks of cancer-specific (HR, 3.31; 95% CI, 1.37-8.03, P=0.01) and CVD cause (HR, 3.18; 95% CI, 1.44-7.02, P <0.001) mortality compared to individuals with normal weight. Being overweight was associated with significantly lower risks of non-cancer, non-CVD cause mortality (HR, 0.66; 95% CI, 0.51-0.87, P < 0.001). Class 1 obesity was associated with significantly reduced risks of all-cause (HR, 0.78; 95% CI, 0.61-0.99, P=0.04), and non-cancer, non-CVD cause (HR, 0.60; 95% CI, 0.42-0.86, P=0.01) mortality. A higher risk of CVD-related mortality (HR, 2.35; 95% CI, 1.07-5.18, P=0.03) was observed in class 3 obesity cases. Lower risks of all-cause mortality were detected in men (overweight, HR, 0.76; 95% CI, 0.59-0.99, P=0.04; class 1 obesity, HR, 0.69; 95% CI, 0.49-0.98, P=0.04) but not in woman, in never-smokers (class 1 obesity, HR, 0.61; 95% CI, 0.41-0.90, P=0.01) and former smokers (overweight, HR, 0.77; 95% CI, 0.60-0.98, P=0.04) but not in current smokers; in obesity-related cancer (class 2 obesity, HR, 0.49; 95% CI, 0.27-0.89, P=0.01) but not in non-obesity-related cancers. Conclusions: In the United States, cancer survivors with overweight or moderate obesity (class 1 or class 2 obesity) demonstrated a lower risk of all-cause and noncancer, non-CVD cause mortality.